Problematik Perkawinan Di Bawah Umur di Kota Kendari - Kamaruddin Kamaruddin (Institut Agama Islam Negeri (IAIN) Kendari, 2017)
The study entitled problematic marriage under Age in Kendari will be discussed and restricted to the issue of underage marriage is problematic particularly in the city of Kendari. Based on the description in the background of the problem can be formulated formulation of the problem posed in this study is: 1.How can the objective conditions of underage marriage in the city of Kendari? 2. What factors are affecting the underage marriage in the city of Kendari? 3. How Efforts are being made to the impact of underage marriages in the city of Kendari. The research objective is 1. To know and analyze the objective conditions of underage marriage in the city of Kendari. 2. To identify and analyze the factors that influence underage marriage in the City of Kendari.3. Know and analyze the impact of efforts made against underage marriage in the city ofKendari. Based on the explanation and discussion of the results of research related to underage marriages in Kendari, it can be concluded as follows: 1. Objective conditions underage marriage in Kendari is still going on and is still done by the residents of the mostly occurs due to pregnancy early, the fact is certainly contrary to the Law No. 1 of 1974 and the legal theory positivisme.2.The factors that influence underage marriage in Kendari are (1) low education, (2) a weak economy, (3) public awareness is still lacking, (4) cultural or environmental. 3. Efforts to do in reducing the impact of underage marriage is a massive socialization, bring awareness to the children of the bride about the benefits and dangers of underage marriage.